Ta’lim Ilmu Fardhu “ain Terhadap Mad’u di Era Digital - Anita Anita (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
A person's religiosity can be reflected through their understanding of Islamic teachings and the extent to which they practice them in daily life. Acts such as purification from impurities, performing ablution (wudu), and prayer (salah) often serve as indicators of a Muslim’s mastery of fard ‘ain knowledge. Fard ‘ain knowledge refers to the essential religious sciences that are obligatory for every Muslim to learn and practice, in contrast to fard kifayah knowledge, which is required only for certain individuals or groups to fulfill communal obligations.However, many Muslims tend to prioritize fard kifayah knowledge while neglecting fard ‘ain knowledge. This imbalance has become more apparent with the rise of digital media as a platform for acquiring and disseminating religious knowledge, including the practice of religious rituals online. Nevertheless, learning religion is not merely about consuming information; it requires verification and guidance from qualified scholars (ulama), religious teachers (ustadz), or Islamic instructors (teungku or muallim) to ensure the authenticity and correctness of religious understanding.Unsupervised access to religious materials on the internet may lead to misunderstandings, misinterpretations, and even misguidance. To address this issue, the implementation of the ta‘lim method is essential—an approach that emphasizes learning religion directly under the supervision of competent and credible ulama, ustadz, teungku, or muallim within their respective areas of expertise.